Efficient Communication in Distributed Collaboration: A Study of Remote Work Environments - Kurzejamski, Kacper (Efektywna komunikacja w organizacjach rozproszonych: badanie środowisk pracy zdalnej, 2024)
The objective of the study was to analyse the impact of hybrid work arrangements on communication in distributed organisations and identify tools and practices enhancing remote communication, collaboration and leadership. In the theoretical part insight into the characteristics of remote work models was provided and communication as the main challenge and critical success factor was identified. Then the characteristics of communication in remote work was reviewed. The empirical part consists of qualitative research with thematic analysis done with MAXQDA software. The research in the form of semi-structured interviews was conducted among IT employees working in hybrid models in Wrocław. The research comprised the analysis of internal communication processes in three main contexts: operational, social, and change-related. Additionally, the relations between employees on different company hierarchy levels were studied.In the conclusions, the importance of redefining leadership towards a more empathetic approach was highlighted and recommendations on efficient leadership practices were provided.
Kurzejamski, K. (2024). Efficient Communication in Distributed Collaboration: A Study of Remote Work Environments. W J. Radomska & A. Witek-Crabb (Red.), New Trends in Business Management (s. 34–46). https://doi.org/10.15611/2024.30.7.03
Keywords: remote work; distributed organisations; communication; leadership; team management; praca zdalna; organizacje rozproszone; komunikacja; przywództwo; zarządzanie zespołem